Strategi Pengembangan Rejeng Bali Camp untuk Meningkatkan Kunjungan Wisatawan di Kintamani - I Gede Angga Lodita; I Gede Sutarya; I Nyoman Ananda (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2019)
Rejeng Bali Camp is a tourist destination in the Batur Tengah village, Kintamani District which has the characteristics of a mountainous area with beautiful natural scenery. This potential should be able to develop rapidly, but in practice it has not yet developed optimally. Therefore, the question discussed in this article is the strategy for developing the Rejeng Bali Camp. This article is qualitatively research, with data collection through observation, in-depth interviews, survays, and literature study. In this study there are several theories used, namely management theory and perception theory. From the results of this study it is known that 1. Rejeng Bali Camp is one of the developing tourist destinations, with a variety of tourism products offered for tourists such as, eating places by the lake, water tourism, and camping. 2. Tourist perceptions about Rejeng Bali Camp show good results, but there are several factorsthat need to be improved by the manager to maximize the development of Rejeng Bali Camp going forward. 3. With the SWOT analysis it was found that Rejeng Bali Camp will become one of the good and sustainable tourist destinations by taking into account all aspects and systems of development that are correct.